Neonatal birth trauma: identifying new risk factors and short-term outcomes - Parikh, Nirzar Samir; Odhiambo, Collins; McMasters, Holleigh; Borkowski, Grace Kathryn; Cross, Adam; Kopec, Gretchen (Frontiers in Pediatrics, 2025)
BackgroundAdvancements in prenatal diagnosis and obstetric care have changed the epidemiology of neonatal birth trauma in developed countries. Improving women's access to health care is key to preventing, detecting, and treating conditions that increase pregnancy complications and adverse neonatal outcomes.ObjectiveTo identify new risk factors—focusing on social determinants of health—and short-term outcomes associated with neonatal birth trauma.Study designTerm neonates with unexpected complications born between January 1, 2019, and March 31, 2023, at 10 diverse hospitals in our health system were identified using Perinatal Care-06 coding. Maternal and neonatal charts were reviewed and recorded in REDCap. Neonates with and without birth trauma were assigned to case and control groups, respectively. Risk factors were identified using Pearson chi-square tests and multivariable logistic regression.ResultsOf 711 neonates, 187 (26.3%) experienced birth trauma, primarily scalp injuries (Caput Succedaneum 42%, Ecchymosis/Bruising 27%). There were no significant differences in race, language barriers, insurance type, marital status, prenatal care access, mean household income (zip code), gestational age, maternal height, birth weight, or head circumference (all p > 0.05). Significant differences were observed in maternal age (p = 0.042), gravidity (p = 0.04), and parity (p = 0.002), with affected mothers being younger, with fewer pregnancies and lower parity. Mothers with chronic or gestational hypertension, with or without preeclampsia, had higher odds of neonatal birth trauma (OR = 1.582, 95% CI: 1.081–2.316, p = 0.018). Emergent deliveries nearly tripled the odds (OR = 2.8, 95% CI: 1.934–4.054, p < 0.001). Neonates exposed to maternal epidural anesthesia were more likely to suffer from birth trauma (77.5 vs. 51.7%, p < 0.001).ConclusionSocial determinants and prenatal care access did not significantly impact birth trauma. However, hypertension, exposure to epidural anesthesia and emergent delivery were associated with an increased risk.